Analysis of branching ratio of telecommunication stocks in thailand using hawkes process - Seksiri,N. (Springer Verlag, 2015)
© Springer International Publishing Switzerland 2015. The aim of the research is to study the branching ratios of the telecommunication stocks in Thailand, ADVANC and DTAC, both listed on the Stock Exchange of Thailand (SET). The branching ratio is the parameter defined in the Hawkes process and directly measures the influential degree of endogeneity. The results indicate to what extent the stock price changes are affected by internal factors. The study found that the branching ratio of ADVANC is at 29%, which means ADVANCs price change is only 29%, caused by internal factors, while the remaining 71% derives from external factors. Meanwhile, DTACs branching ratio is at 55%, meaning DTACs price change is 55% due to internal factors and 45% due to external. Knowing to what extent the stock price is affected by external factors can strengthen investor strategy. Stocks with a low branching ratio are more speculative than those having a high branching ratio.